Evaluating the Effectiveness of United Nations Peacebuilding Operations - Osman, Shihab Sulaiman Abdalla; Elbashir, Hanan Abd Elmoniem Gubara; Hosnia , Ahmed O.K (Journal of Ecohumanism, 2024)
The study addresses how to find legal solutions that are accepted by most countries in the world within the framework of maintaining international peace and security by ensuring the international public good, reflecting the dissemination of justice among all the peoples of the world. It also emphasizes equality for all individuals within a single nation under the concept of citizenship, away from discrimination. Recently, the intensity and violence of conflicts and armed disputes between countries have increased, along with the suffering of people everywhere on earth. These tragedies witnessed by millions of people have driven the need to think about mechanisms by which humans can resolve their disputes without resorting to the use of armed force to protect their vital and strategic interests. Attention has turned to what represents the international community, which is supposed to be impartial and objective, in addition to the expertise gained from exposure to many such difficult situations where the parties involved are suspicious of each other. The United Nations was the means to maintain international peace and security. However, over time, it became evident to everyone that this organization, despite its significant international standing, was unable to maintain peace and security in many regions around the world. This led to widespread calls for reforming the United Nations system, which revolves around the five major victorious countries of World War II, to become an organization that truly represents the international community and not just the five permanent members of the Security Council. The international community, through the United Nations General Assembly, should play an active role in compelling all parties in a dispute to resort to the International Court of Justice, whose rulings would be binding on all parties, at least in matters of a humanitarian nature. Considering the above, the research will demonstrate the significant shortcomings in the role of the United Nations in building peace and economic reconstruction of countries emerging from chaos and armed conflict. Therefore, it is necessary to activate the international system to consider the humanitarian aspects related to the post-armed conflict phase by amending the United Nations Charter to clearly include the roles to be undertaken by each member of the international.